Frequency, severity, and impact on daily life of delayed and intercycle chemotherapy-induced nausea, vomiting, and retching. Issue 6 (December 2021) - Gonella, Silvia; Di Massimo, Dino S.; Mistrangelo, Marinella; Numico, Gianmauro; Berchialla, Paola; Di Giulio, Paola
Introduction: Chemotherapy-induced nausea, vomiting, and retching (CINVR) remains a common side effect of treatment. Most previous studies have focused on vomiting control; nausea and retching have been less explored. This study aimed at describing the incidence, severity, and impact on daily life (IDL) of CINVR in the acute (0–24 hours), delayed (>24–120 hours), and overall (0–120 hours) postchemotherapy periods and beyond 120 hours (until next chemotherapy administration); and the pharmacologic and nonpharmacologic strategies adopted by patients to relieve symptoms. Methods: This was a single-center, cross-sectional study of 60 patients undergoing chemotherapy. Participants reported the frequency, severity, and IDL of CINVR from the day of chemotherapy administration up to 120 hours thereafter and nausea and vomiting that occurred beyond 120 hours, as well as pharmacologic and nonpharmacologic remedies used. Results: Forty-seven (78.3%, 95% confidence interval [CI] 66.4–86.9), 37 (61.7%, 95% CI 49.0–72.9), and 35 (58.3%, 95% CI 45.7–69.9) patients reported no nausea (Numeric Rating Scale ⩽1), vomiting, or retching in the acute, delayed, and overall periods, respectively. Nausea was more frequent, more severe, and had a greater IDL than did vomiting and retching across the overall observation period; beyond 120 hours, 11 (18.3%, 95% CI 10.6–29.9) patients reported nausea and none reported vomiting, with a median IDL of 1/10 (interquartile range: 0.75–5.00; 95% CI 0–7.6). Metoclopramide (n = 57 administrations), dexamethasone (n = 28), eating small servings of food (n = 13), and aloe (n = 11) were the most commonly used rescue therapies. Conclusions: Future studies should set hard outcomes, such as the absence of any symptoms, as a primary end point, and these should be assessed across and beyond the 120-hour period.